Viscoelastic properties of soy protein isolate - pectin blends: Richer than those of a simple composite material. (May 2018) - Dekkers, Birgit L.; Boom, Remko M.; van der Goot, Atze Jan
Abstract: Concentrated soy protein isolate (SPI) – pectin blends acquire fibrous textures by shear-induced structuring while heating. The objective of this study was to determine the viscoelastic properties of concentrated SPI-pectin blends under similar conditions as during shear-induced structuring, and after cooling. A closed cavity rheometer was used to measure these properties under these conditions. At 140 °C, SPI and pectin had both a lower G* than the blend of the two and also showed a different behavior in time. Hence, the viscoelastic properties of the blend are richer than those of a simple composite material with stable physical phase properties. In addition, the G′ pectin was much lower compared with the G′ SPI and G′ SPI-pectin upon cooling, confirming that pectin formed a weak dispersed phase. The results can be explained by considering that the viscoelastic properties of the blend are influenced by thermal degradation of the pectin phase. This degradation leads to: i ) release of galacturonic acid, ii ) lowering of the pH, and iii ) water redistribution from the SPI towards the pectin phase. The relative importance of those effects are evaluated. Graphical abstract: Highlights: Viscoelastic properties are studied to explain phenomena observed in shear-induced structuring. Viscoelastic properties of SPI-pectin blends are influenced by temperature and shear. A soy protein isolate – pectin blend cannot be regarded as a simple composite material. The ability of the network to recover is low at 140 °C. Pectin degrades at 140 °C resulting in lowering of pH, release of galacturonic acid, and water redistribution.